FRI0338 Therapeutic Effect of A New Histone Deacetylase 6 Inhibitor, Ckd-L, on Collagen Induced Arthritis and Peripheral Blood Mononuclear Cells from Patients with Rheumatoid Arthritis in Vitro. (10th June 2014) - Oh, B.; Lim, H.; Ko, E.H.; Ha, N.; Yoo, H.J.; Park, J.K.; Lee, E.Y.; Lee, E.B.; Song, Y.W.
Abstract : Background: Epigenetic regulation plays an important role in inflammatory arthritis, including rheumatoid arthritis (RA). Histone deacetylase inhibitor (HDACi) has been recently reported to have therapeutic effect in collagen induced arthritis (CIA). CKD-L is a new HDAC6i developed by Chong Kun Dang Pharmaceutical Corporation. Objectives: We investigated the therapeutic effect of selective HDAC6 inhibitors (CKD-L and Tubastatin A) on RA peripheral blood mononuclear cells (PBMC) and CIA. Methods: RA PBMCs were stimulated with lipopolysaccharide 100 ng/ml and incubated with HDAC6i (CKD-L and Tubastatin A, 0.01-5 μM) for 24 hours. Cytokine production of the cell supernatant was determined by multiplex cytokine assay. Induced T reg (iTreg) cells were induced with anti-CD3 Ab, anti-CD28 Ab, IL-2, TGF-b and 1, 25(OH)2 VD3 . iTreg cells were incubated for 3 days with 5 uM carboxyfluorescein succinimidyl ester (CFSE)-stained CD4 + CD25 – T (Teff) cells in the presence of anti-CD3/CD28 Abs and HDAC6i. Proliferation of Teff cells was analysed by flow cytometry. CIA was induced by bovine type II collagen (CII) in DBA/1 mouse. Mice were treated with vehicle, CKD-L or Tubastatin 30 mg/kg by subcutaneous injection every 3 days for 18 days. Mouse iTreg cells were treated with HDAC6i for 24 hours and cytotoxic T lymphocyte associated protein 4 (CTLA-4) expression was analysed by flow cytometry. Proliferation of Teff cells was also analysed. Results: In RA PBMC, TNF-α was decreased after treatment with CKD-L (p<0.001) and Tubastatin A (p<0.001). IL-10 was increased after treatment with CKD-L (p=0.051) and Tubastatin A (p=0.083). IL-1 and IL-6 did not change with CKD-L or Tubastatin A. In co-culture with iTreg cells and Teff cells, CKD-L efficiently inhibited the proliferation of Teff cells (13.9%) compared to control (32.6%). Tubastatin A had no effect on proliferation (30.1%). In CIA, CKD-L and Tubastatin A significantly reduced arthritis score. CTLA-4 expression in CD4 + CD25 + Foxp3 + cell increased after treatment of CKD-L (P<0.001) and Tubastatin A (P<0.05). And proliferation of mouse Teff cells was inhibited after treatment with CKD-L (67.8%) and Tubastatin A (68.3%) compared to control (80.1%). Conclusions: CKD-L and Tubastatin A decreased TNF-α and increased IL-10 in RA PBMC. iTreg cells efficiently inhibited the proliferation of effector T cells in the presence of CKD-L, but not Tubastatin A. In CIA, arthritis score was significantly reduced by CKD-L or Tubastatin A. These results suggest that CKD-L increase regulatory T cell function and has beneficial effect in the treatment of RA. References: Saouaf SJ et al. Deacetylase inhibition increases regulatory T cell function and decreases incidence and severity of collagen-induced arthritis. Exp Mol Pathol. 2009;87:99-104 Kang SW et al. 1, 25-Dihyroxyvitamin D3 promotes FOXP3 expression via binding to Vitamin D response elements in its conserved noncoding sequence region. J Immunol 1;188(11):5276-822. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5397